The Pearling Transition Provides Evidence of Force-Driven Endosomal Tubulation during Salmonella Infection - Yunfeng Gao (American Society for Microbiology, 2018)
ABSTRACT Bacterial pathogens exploit eukaryotic pathways for their own end. Upon ingestion, Salmonella enterica serovar Typhimurium passes through the stomach and then catalyzes its uptake across the intestinal epithelium. It survives and replicates in an acidic vacuole through the action of virulence factors secreted by a type three secretion system located on Salmonella pathogenicity island 2 (SPI-2). Two secreted effectors, SifA and SseJ, are sufficient for endosomal tubule formation, which modifies the vacuole and enables Salmonella to replicate within it. Two-color, superresolution imaging of the secreted virulence factor SseJ and tubulin revealed that SseJ formed clusters of conserved size at regular, periodic intervals in the host cytoplasm. Analysis of SseJ clustering indicated the presence of a pearling effect, which is a force-driven, osmotically sensitive process. The pearling transition is an instability driven by membranes under tension; it is induced by hypotonic or hypertonic buffer exchange and leads to the formation of beadlike structures of similar size and regular spacing. Reducing the osmolality of the fixation conditions using glutaraldehyde enabled visualization of continuous and intact tubules. Correlation analysis revealed that SseJ was colocalized with the motor protein kinesin. Tubulation of the endoplasmic reticulum is driven by microtubule motors, and in the present work, we describe how Salmonella has coopted the microtubule motor kinesin to drive the force-dependent process of endosomal tubulation. Thus, endosomal tubule formation is a force-driven process catalyzed by Salmonella virulence factors secreted into the host cytoplasm during infection. IMPORTANCE This study represents the first example of using two-color, superresolution imaging to analyze the secretion of Salmonella virulence factors as they are secreted from the SPI-2 type three secretion system. Previous studies imaged effectors that were overexpressed in the host cytoplasm. The present work reveals an unusual force-driven process, the pearling transition, which indicates that Salmonella-induced filaments are under force through the interactions of effector molecules with the motor protein kinesin. This work provides a caution by highlighting how fixation conditions can influence the images observed.